Nitric Oxide Synthase Inhibition as a Neuroprotective Strategy Following Hypoxic–Ischemic Encephalopathy: Evidence From Animal Studies - Favié, Laurent M. A.; Cox, Arlette R.; van den Hoogen, Agnes; Nijboer, Cora H. A.; Peeters-Scholte, Cacha M. P. C. D.; van Bel, Frank; Egberts, Toine C. G.; Rademaker, Carin M. A.; Groenendaal, Floris (Frontiers in Neurology, 2018)
Background: Hypoxic-ischemic encephalopathy following perinatal asphyxia is a leading cause of neonatal death and disability worldwide. Treatment with therapeutic hypothermia reduced adverse outcome from 60% to 45%. Additional strategies are urgently needed to further improve the outcome of these neonates. Inhibition of nitric oxide synthase is a potential neuroprotective target. This article reviews the evidence of neuroprotection by nitric oxide synthesis inhibition in animal models. Methods: Literature search using the EMBASE, Medline, Cochrane and PubMed databases. Studies comparing nitric oxide synthase inhibition to placebo with neuroprotective outcome measures in relevant animal models were included. Methodologic quality of the included studies was assessed. Results: 26 studies were included using non-selective or selective nitric oxide synthase inhibition in rat, piglet, sheep or rabbit animal models. A large variety in outcome measures was reported. Outcome measures were grouped as either histological, biological or neurobehavioral. Both non-selective and selective inhibitors show neuroprotective properties in one or more outcome measures. Methodologic quality was either low or moderate for all studies. Conclusion: Inhibition of nitric oxide synthesis is a promising strategy for additional neuroprotection. In humans, intervention can only take place after the onset of the hypoxic-ischemic event. Therefore, combined inhibition of neuronal and inducible nitric oxide synthase seems the most likely candidate for human clinical trials. Future studies should determine its safety and effectiveness in neonates as well as a potential sex specific neuroprotective effect. Researchers should strive to improve methodologic quality of animal intervention studies by using a systematic approach in conducting and reporting of these studies.